2010
DOI: 10.1186/1465-9921-11-162
|View full text |Cite
|
Sign up to set email alerts
|

Airway branching morphogenesis in three dimensional culture

Abstract: BackgroundLungs develop from the fetal digestive tract where epithelium invades the vascular rich stroma in a process called branching morphogenesis. In organogenesis, endothelial cells have been shown to be important for morphogenesis and the maintenance of organ structure. The aim of this study was to recapitulate human lung morphogenesis in vitro by establishing a three dimensional (3D) co-culture model where lung epithelial cells were cultured in endothelial-rich stroma.MethodsWe used a human bronchial epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 36 publications
5
86
0
1
Order By: Relevance
“…3D cultures were performed as previously described. 26 Production of Lentivirus and Cell Transduction Lentiviral transduction was performed as previously described. 28 In short, plasmids containing scrambled hairpin (pLKO.1 shSCR; Addgene plasmid 17920) 29 or shRNA against p63 (shp63alpha pLKO.1 puro; Addgene plasmid 19120) 30 were used with packaging plasmids (psPAX2 and pMD2.G) (Addgene plasmids 12260 and 12259, respectively) to generate viral titer in HEK-293 T cells using Arrest-in (Open Biosystems).…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…3D cultures were performed as previously described. 26 Production of Lentivirus and Cell Transduction Lentiviral transduction was performed as previously described. 28 In short, plasmids containing scrambled hairpin (pLKO.1 shSCR; Addgene plasmid 17920) 29 or shRNA against p63 (shp63alpha pLKO.1 puro; Addgene plasmid 19120) 30 were used with packaging plasmids (psPAX2 and pMD2.G) (Addgene plasmids 12260 and 12259, respectively) to generate viral titer in HEK-293 T cells using Arrest-in (Open Biosystems).…”
Section: Cell Culturementioning
confidence: 99%
“…25 In addition, this cell line forms bronchio-alveolarlike structures in three-dimensional co-culture with endothelial cells. 25,26 In this study, we focus on the p63-positive lung epithelial basal cell as one potential progenitor cell for the myofibroblast in IPF.…”
mentioning
confidence: 99%
“…1A), although these colonies were not accompanied by a branching structure. VA10 cells form a branching structure in rBM when co‐cultured with HUVECs 18, but we did not observe branching colonies of HBE135 cells in co‐culture with HUVECs (Fig. 1B).…”
Section: Resultsmentioning
confidence: 70%
“…reported that the human BEC line VA‐10 forms polarized spherical colonies when grown in 3D culture 18. We first cultured HBE135 cells alone in rBM at the same concentration (333 cells per 100 μl rBM), but the HBE135 cells did not form colonies (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation